2020
DOI: 10.1055/s-0040-1718878
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Second Stage of Labor and Anal Sphincter Injury in a Contemporary Cohort of Term Nulliparas

Abstract: Objective This study aimed to assess whether a prolonged second stage of labor is an independent predictor of obstetric anal sphincter injury (OASI) in a contemporary cohort of nulliparous and term parturients, and to evaluate whether predelivery factors can accurately predict OASI. Study Design This was a nested case-control study within a cohort of consecutive nulliparous term parturients with a singleton gestation who underwent a vaginal delivery at a single institution between January 2014 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…The risks of caesarean delivery (CD), operative vaginal delivery, and maternal complications, including postpartum haemorrhage, chorioamnionitis, endometritis, postpartum fever and advanced perineal lacerations, increase when the second stage duration is prolonged. [8][9][10][11][12][13] The effect of active first stage duration is less investigated, which is of concern as labour is a continuous process and its first and second stages are closely interrelated. 14,15 The few studies that exist have indicated an association between active first stage duration and composite adverse maternal outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risks of caesarean delivery (CD), operative vaginal delivery, and maternal complications, including postpartum haemorrhage, chorioamnionitis, endometritis, postpartum fever and advanced perineal lacerations, increase when the second stage duration is prolonged. [8][9][10][11][12][13] The effect of active first stage duration is less investigated, which is of concern as labour is a continuous process and its first and second stages are closely interrelated. 14,15 The few studies that exist have indicated an association between active first stage duration and composite adverse maternal outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…A longer second stage labour duration has been associated with increased maternal morbidity in numerous studies. The risks of caesarean delivery (CD), operative vaginal delivery, and maternal complications, including postpartum haemorrhage, chorioamnionitis, endometritis, postpartum fever and advanced perineal lacerations, increase when the second stage duration is prolonged 8–13 . The effect of active first stage duration is less investigated, which is of concern as labour is a continuous process and its first and second stages are closely interrelated 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of OASIS in modern obstetric practice varies in different populations, ranging from an incidence of less than 1% to an incidence of 6% [ 1 , 2 , 3 , 4 ]. The risk factors for OASIS are similar worldwide and include primiparity, birthweight >4000 g, instrumental assisted deliveries, persistent occiput posterior presentation, a prolonged second stage of labor, median episiotomy, and previous OASIS [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. In addition, there is controversy about other possible risk factors such as vaginal birth after a cesarean section, maternal age, ethnicity, and more.…”
Section: Introductionmentioning
confidence: 99%
“…There is a large number of studies describing birth outcomes in relation to the second stage, but most of them lack a division of the passive and active second stage. A prolonged second stage has been associated with adverse maternal outcomes: postpartum haemorrhage (PPH), infection, obstetric anal sphincter injury (OASI) (71), IB, CS, and episiotomies (72)(73)(74)(75)(76)(77)(78)(79) in nulli-and parous women. A new policy in labour management in the United States in 2014 aimed to reduce the CS rate for nulliparous women by adding an additional hour before diagnosing a prolonged second stage.…”
Section: Maternal Outcomesmentioning
confidence: 99%